Attitudes and Self-Reported Competencies in Advocacy Among OB/GYN Residents [25I]. Issue 1 (May 2017) - Hall, Evelyn; Quinlan, Maura; Gerber, Susan
Abstract : INTRODUCTION: The American College of Obstetricians and Gynecologists recognizes that education and training in advocacy is an important component of postgraduate education. However, there is little published literature on how to best teach advocacy to residents. METHODS: We administered an IRB-approved, self-reported, cross-sectional study of ob/gyn residents at Northwestern. The survey employed a 5-point Likert scale and was designed to assess residents' experiences with advocacy training. RESULTS: Forty of 46 residents completed the survey. Among respondents, 95% felt that political advocacy is important to the field of ob/gyn, 92.5% believed government policies will affect their career, and 90% believed that formal training in advocacy and policy should be a part of residency training. Yet, only 38.4% felt that they had at least a basic understanding of Medicare billing and reimbursement policy, and 40% felt that their residency program encouraged advocacy. Residents did not feel that testing advocacy on national exams would improve their knowledge base in the area. While involvement in advocacy was common during medical school (90%), only 22.5% of residents were currently engaged in advocacy activities, and 27.5% were undecided if they would engage in advocacy during training. Common barriers reported were time, stress, and lack of knowledge on how to become meaningfully involved in advocacy work. CONCLUSION: Residents show high interest in advocacy, yet experience multiple barriers to becoming involved and report knowledge gaps on specific policy topics. Further research is needed to improve education and opportunities in advocacy for residents.